Language Learning Approaches: A Study Meta-Analysis of Vocabulary Mastery in EFL Learners - Ferri Hidayad; Despita Despita; Fitri Novia; Muhammad Bambang Purwanto (International Journal of Digital Learning on Languages and Arts (IJODLLA), 2024)
To determine whether language learning is feasible, numerous researchers from around the world have studied this area; nevertheless, no real solution has yet been put forth in this regard. It is simpler to gain a command of the second language or even speak it fluently with linguistic comprehension and knowledge. This study does a meta-analysis of three study programs to examine the applicability of the various strategies and methodologies suggested in this research project related vocabulary learning or lexical knowledge. The results demonstrated that the learners' lexical knowledge strategies encompassed cognitive, metacognitive, social, willpower, and memory techniques. Additionally, competent people preferred making assumptions based on context and scenario and employing dictionary references. Additionally, this study looked into the relationship between the background, circumstance, approach, context, and therapy using a vocabulary acquisition strategy. The findings indicated that while the instructors used particular teaching methods in accordance with their curricula and preferred distinct methods, the L2 beginners came from diverse backgrounds and situations. The study's findings suggest that in order to effectively encourage the new EFL learners to improve their vocabulary, the instructors must be fully aware of the significance of using an appropriate strategy for English language teaching (ELT) in STKIP Muhammadiyah Pagaralam.